MEMANFAATKAN TINGGINYA BEBAN TETAP UNTUK MEMPEROLEH KEUNTUNGAN YANG OPTIMAL - Lies Indriyatni (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
Some companies, like PT. Telkom, PT. Garuda or some tourist object management companies, obviously need a big infestation for allocating satellite, distribution network, aero planes and some uninstalled utilities. When everything has installed or available, it leaves to the companies to think how to sell the pulses or the tickets as many as possible.It’s concerned that many companies which budget structures contain high fixed costs will face many risks ahead. Companies will be very sensitive to the changes, both in sales volume and the variable costs. These things have been undeniable anymore so that it becomes not relevant to be used as basic accounting in decision making. Instead of being worried by the risks, it’s better to make advantages from the risks itself. It can be done by improving the sales by some other ways; likes setting the more challenging price or fare; become more aggressive in promotion or wider the distribution.The more important thing is not just look on short term profits but also the more important is the long term profits.